Characterizing Selected Sorghum Grain Varieties and Evaluating the Suitability of Their Malt Extracts for Cultivating Microbial Biomass - Stellah Byakika; Ivan Muzira Mukisa; Yusuf Byenkya Byaruhanga (International Journal of Food Science)
Microbial biomass is cultivated for different technological applications including food processing, medicine, waste management, and research. The conventional growth media used are generally expensive thus necessitating the development of more affordable alternatives. In this study, four sorghum grain varieties, SESO 1, SESO 3, Epuripur, and Eyera, and their malt extracts were characterized which is aimed at determining their suitability for growing microbial biomass. The varieties had kernel length, kernel width, kernel thickness, and thousand kernel weigh equivalent to 3.8-4.3 mm, 3.2-4.5 mm, 2.4-2.8 mm, and 12.4-20.2 g, respectively. SESO 1 and Epuripur had corneous endosperm textures whereas those of SESO 3 and Eyera were intermediate and floury, respectively. Varieties had germinative energies>90% and total defects<8%. SESO 3 had the highest (p<0.05) crude protein (10.8±0.3%) and dietary fiber (22.5±0.4%) whereas Epuripur had the highest (p<0.05) starch (81.6±0.0%) and crude fat (2.9±0.1%). There was no significant difference (p>0.05) in the ash contents (2.1±0.0%). The total sugars, free amino nitrogen, condensed tannins, and pH of the malt extracts were 106-116 g/L, 70-78 mg/L, 0.1-0.6 mg/mL, and 5.5-5.7, respectively. The composition of the sorghum malt extracts suggests their potential for use in cultivating microbial biomass.